2019
DOI: 10.3390/cells9010001
|View full text |Cite
|
Sign up to set email alerts
|

Repaglinide Silences the FOXO3/Lumican Axis and Represses the Associated Metastatic Potential of Neuronal Cancer Cells

Abstract: The transcription factor FOXO3 is associated with poor outcome in high-stage neuroblastoma (NB), as it facilitates chemoprotection and tumor angiogenesis. In other tumor entities, FOXO3 stimulates metastasis formation, one of the biggest challenges in the treatment of aggressive NB. However, the impact of FOXO3 on the metastatic potential of neuronal tumor cells remains largely unknown. In the present study, we uncover the small leucine-rich proteoglycan family member lumican (LUM) as a FOXO3-regulated gene th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 48 publications
(120 reference statements)
0
19
0
Order By: Relevance
“…Other cancer cell types that have been studied regarding the lumican-dependent motility effects include lung, breast, colon, liver, bladder, and pancreatic cancer, as well as neuroblastomas [3,61,62,65,69,73,79,80,88,94,95].…”
Section: Lumican Modulates Cancer Cell Motilitymentioning
confidence: 99%
See 3 more Smart Citations
“…Other cancer cell types that have been studied regarding the lumican-dependent motility effects include lung, breast, colon, liver, bladder, and pancreatic cancer, as well as neuroblastomas [3,61,62,65,69,73,79,80,88,94,95].…”
Section: Lumican Modulates Cancer Cell Motilitymentioning
confidence: 99%
“…Lumican pro-tumorigenic effects are also observed in gastric, bladder, colon, clear cell renal, and liver cancers [ 59 , 60 , 61 , 62 ]. A high lumican expression in gastric cancer tissues indicates a poor patient prognosis [ 48 ].…”
Section: Lumican Structure Function and Expression-correlation With Carcinogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…Further research found that decorin and podocan are involved in the development of diabetic nephropathy 10,19 . In addition, some studies have found that SLRPs (decorin, biglycan, lumican, TSK, osteoadherin, osteoglycin, asporin) are shown to be involved in the pathogenesis of tumors by modulating the proliferation, apoptosis, invasion, and migration of the cancer cells 8,20–24 …”
Section: Introductionmentioning
confidence: 99%